2014
DOI: 10.1002/mds.25982
|View full text |Cite
|
Sign up to set email alerts
|

Cortical thinning associated with mild cognitive impairment in Parkinson's disease

Abstract: The aim of this study was to investigate patterns of cortical atrophy associated with mild cognitive impairment in a large sample of nondemented Parkinson's disease (PD) patients, and its relation with specific neuropsychological deficits. Magnetic resonance imaging (MRI) and neuropsychological assessment were performed in a sample of 90 nondemented PD patients and 32 healthy controls. All underwent a neuropsychological battery including tests that assess different cognitive domains: attention and working memo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

21
92
2
4

Year Published

2015
2015
2021
2021

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 103 publications
(122 citation statements)
references
References 46 publications
21
92
2
4
Order By: Relevance
“…(2012) found occipital and inferior parietal hypometabolism in association with more severe cognitive impairment and dementia using fluorodeoxyglucose positron emission tomography34. Finally, in structural MRI studies, PD-MCI patients have been shown to have occipital as well as posterior parietal and temporal cortical thinning3536. Our findings add to this putative relationship between posterior cortical alterations and cognitive impairment in PD.…”
Section: Discussionsupporting
confidence: 52%
“…(2012) found occipital and inferior parietal hypometabolism in association with more severe cognitive impairment and dementia using fluorodeoxyglucose positron emission tomography34. Finally, in structural MRI studies, PD-MCI patients have been shown to have occipital as well as posterior parietal and temporal cortical thinning3536. Our findings add to this putative relationship between posterior cortical alterations and cognitive impairment in PD.…”
Section: Discussionsupporting
confidence: 52%
“…Gray matter atrophy in PD has been reported by a number of groups (Hwang et al, 2013; Ibarretxe-Bilbao et al, 2012; Lewis et al, 2016; Pereira et al, 2014; Ramirez-Ruiz et al, 2007; Segura et al, 2014; Song et al, 2011; Tinaz et al, 2011; Zhang et al, 2014), and the current study confirmed these findings in a longitudinal cohort. On the other hand, past research has yielded inconsistent results regarding the extent and nature of white matter involvement in PD.…”
Section: Discussionsupporting
confidence: 90%
“…Cognitive scores in Parkinson's disease patients correlate with dorso-fronto parietal connectivity; inhibited subcortical primary sensory activation; and preserved nigrostriatal pathways in resting-state functional magnetic resonance imaging (fMRI), but not with presynaptic dopaminergic uptake [17]. Atrophy in various cortical regions is associated with neuropsychiatric symptoms [18 & ], as well as MCI in some studies [19,20,21 & ,22 & ,23], though others found no such differences in PD-MCI compared to Parkinson's disease without MCI [24,25]. The expected effect of MCI on the subcortical regions is even less clear, though hippocampal atrophy was found to predict conversion to PD-MCI and to dementia from PD-MCI in a longitudinal study [26].…”
Section: Neuroimaging Mild Cognitive Impairmentmentioning
confidence: 99%